Write the following cubes in expanded form:
(i)
(ii)
(iii)
(iv)
(i) (2x + 1)3
Using identity,
(a + b)3 = a3 + b3 + 3ab (a + b)
(2x + 1)3 = (2x)3 + (1)3 + (3 * 2 * 1) (2x + 1)
= 8x3 + 1 + 6x (2x + 1)
= 8x3 + 12x2 + 6x + 1
(ii) Using identity,
(a – b)3 = a3 – b3 – 3ab (a – b)
(2a – 3b)3 = (2a)3 – (3b)3 – (3 * 2a * 3b) (2a – 3b)
= 8a3 – 27b3 – 18ab (2a – 3b)
= 8a3 – 27b3 – 36a2b + 54ab2
(iii) Using identity,
(a – b)3 = a3 – b3 – 3ab (a – b)
(x + 1)3 = (
x)3 + 13 + (3 *
x * 1) (
x + 1)
= x3 + 1 +
x (
x + 1)
= x3 + 1 +
x2 +
x
= x3 +
x2 +
x + 1
(iv) Using identity,
(a – b)3 = a3 – b3 – 3ab (a – b)
(x - y)3 = (x)3 – (
y)3 – (3 * x *
y) (x -
y)
= x3 - y3 – 2xy (x -
y)
= x3 - y3 – 2x2y +
xy2